Comparative evaluation of instrumentation time, obturation time, and radiographic quality of obturation using two rotary systems and manual technique for primary molar pulpectomies - In vivo study - Heeral Sureshkumar Shah; Vishwas Mohanrao Patil; Ananth P Kamath; Aditi Anmol Mathur (Wolters Kluwer Medknow Publications, 2021)
Background: Ideal pulpectomy for primary dentition demands fast, simple procedures, with short treatment times and minimal appointments. Recently, exclusive pediatric rotary files are available for use in primary teeth. There is a paucity of literature on the clinical efficacy of pediatric rotary files. Hence, this study was planned to evaluate and compare pediatric rotary files and K-files. Aim: The aim of this study was to evaluate and compare instrumentation time, obturation time, and radiographic quality of obturation using rotary systems (Kedo-S; Pro-AF Baby GOLD files) and manual (K-files) technique in primary molar pulpectomies. Materials and Methods: Forty-five primary mandibular molars from 42 children aged 5-9 were selected. Single-visit pulpectomy was performed after dividing selected teeth into three equal groups: (i) K-files, (ii) Kedo-S files, (iii) Pro-AF Baby GOLD files. Instrumentation and obturation times were recorded during the procedure. Immediate postoperative radiographs were taken and evaluated later for obturation quality by two independent evaluators blinded to the instrumentation technique. The results were then statistically analyzed. Results: Kedo-S (Group II) files required the least instrumentation time followed by Pro-AF (Group III) and K-files (Group I). The superior quality of obturation in lesser time was achieved using Pro-AF files (Group III) followed by Kedo-S (Group II) and K-files (Group I). Conclusion: Pediatric rotary files are efficient alternatives to hand instrumentation and can be considered as the standard of care in pulpectomies of primary teeth.